Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences; Vol 6 No 1 (2020): KIU Journal of Social Sciences, Vol. 6 No. 1, March 2020, 2020)
This issue of KIU Journal of Social Sciences focuses on Development Administration, Social Psychology, Educational Psychology, Organizational Management, Educational Management, Religious, Peace and Conflict Studies as well as Gender and Literary Studies. The first part of the Journal addresses issues in Development Administration such as Monetaty Policies, Crime Management. Investment in Teacher Education, Tax Administration, Corruption and Corporate Social Resposibility, in Nigeria as well as the politics and effects of removal of ptetoleum subsidy. It is argued in one of the papers that except the Government tackles the status of poverty, stream of unemployment and underemployment in Nigeria, the chances of police efficiency in crime management is doubtful and the development of the country will be hard to achieve. Section two explores the social and cultural factors that affect the academic performance of students in various institutions of learning in the society. One of the papers suggests that students should be thought measures on how to develop their emotional intelligence both by parents and teachers in school. In the Section on Organizational Management, it is recommended that administrators of tertiary institutions and government should endeavour to maintain cordial relationship with their labour force to enhance lecturers’ productivity and or performance. This is drawn from the conclusion that unhealthy labour-management relationship negatively affects lecturers’ performance in tertiary institutions in Taraba State, Nigeria. Papers in Section Four amplify some issues in Religious, Peace and Conflict Studies. Theoretical, methodological and practical implications are discussed in the papers. One of the papers reveals that religious groups play several roles in tilting the policies of Nigeria internal and external dealings as a Muslim leader prefers to work with Muslim administrators while those of Christians have faith in co-Christians irrespective of the competency and experiences of governance of the sect members. This also affects the external relationships these leaders propose or entered into while they are in power. Another paper in this section disclosed that the inequality-insecurity nexus is particularly made daunting by constant intimidation of the lower-class by powerful rich which drives the socially excluded into conflict, terrorism and other behaviour that threaten security. It therefore recommends that the cycle of insecurity occasioned by socioeconomic inequality can only be broken by deliberate policy interventions with political commitment. Papers in Section Five are on Gender and Literary Studies. One of the papers in this section recommends, among others, that Physical Education agencies should work hard with the traditional rulers of the area of study, through seminars, conferences, etc, to educate and create awareness on the rights and importance of women to recreational activities, especially in the zone of study. It also recommended the restructuring of Women’s Education with emphasis on physical activities and recreation for leisure values. The last section is on Educational Management. It is argued in this section that bad reading habit amongst students have significant negative impact on their academic achievement and health condition. One of the recommendations made in the paper is that students should be encouraged to borrow books from the library regularly since this can help them to inculcate reading habits. In summary, this edition of KIU Journal of Social Sciences contains papers that have information on all aspects of human endeavour. Collaborative and cooperative approaches are offered as best approaches for dealing with matters that lead to the instability of communities, societies, economies, and the environment. The theoretical analyses provide opportunities to operationalize the theories discussed in the articles. The authors’ teachings and areas of research must have certainly influenced their perspectives on the diagnoses of the matters they have addressed in their articles.